2021
DOI: 10.3390/molecules27010097
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dia2 Protein Deficiency on the Cell Cycle, Cell Size, and Recruitment of Ctf4 Protein in Saccharomyces cerevisiae

Abstract: Cells have evolved elaborate mechanisms to regulate DNA replication machinery and cell cycles in response to DNA damage and replication stress in order to prevent genomic instability and cancer. The E3 ubiquitin ligase SCFDia2 in S. cerevisiae is involved in the DNA replication and DNA damage stress response, but its effect on cell growth is still unclear. Here, we demonstrate that the absence of Dia2 prolongs the cell cycle by extending both S- and G2/M-phases while, at the same time, activating the S-phase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…It is conceivable that exposure to UV triggers changes in cell cycle progression after the resolution of DNA damage checkpoint activation, leading to enrichment of UV hyper-resistant G2 cells in the growing culture population. Furthermore, it has been shown that prolonging the cell cycle leads to an increase in yeast cell size [ 38 ], which may enhance the UVHR phenotype. The epigenetic nature of the UVHR phenotype suggests that the putative altered cell cycle distribution and associated cell size changes subsequently propagate over multiple cell generations to provide inheritable protection against recurrent UV exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that exposure to UV triggers changes in cell cycle progression after the resolution of DNA damage checkpoint activation, leading to enrichment of UV hyper-resistant G2 cells in the growing culture population. Furthermore, it has been shown that prolonging the cell cycle leads to an increase in yeast cell size [ 38 ], which may enhance the UVHR phenotype. The epigenetic nature of the UVHR phenotype suggests that the putative altered cell cycle distribution and associated cell size changes subsequently propagate over multiple cell generations to provide inheritable protection against recurrent UV exposure.…”
Section: Discussionmentioning
confidence: 99%